Evaluation of the Affymetrix CytoScan® Dx Assay for developmental delay. (February 2014) - Webb, Bryn D; Scharf, Rebecca J; Spear, Emily A; Edelmann, Lisa J; Stroustrup, Annemarie
<x xml:space="preserve">Abstract</x> The goal of molecular cytogenetic testing for children presenting with developmental delay (DD) is to identify or exclude genetic abnormalities that are associated with cognitive, behavioral and/or motor symptoms. Until 2010, chromosome analysis was the standard first-line genetic screening test for evaluation of patients with DD when a specific syndrome was not suspected. In 2010, The American College of Medical Genetics and several other groups recommended chromosomal microarray as the first-line test in children with DDs, multiple congenital anomalies and/or autism. This test is able to detect regions of genomic imbalances at a much finer resolution than G-banded karyotyping. Until recently, no chromosomal microarray testing had been approved by the US FDA. This article focuses on the use of the Affymetrix CytoScan® Dx Assay (Santa Clara, CA, USA), the first chromosomal microarray to receive FDA approval for the genetic evaluation of individuals with DD.